Labour tenancy and the land clearances at Pilgrims Rest - Mabin, Alan (My University, 1985)
Towards the end of August 1951, the manager of Transvaal Gold Mining Estates (TGME) wrote to Rand Mines asking for advice on a 'very embarrassing matter'. The problem he faced was one of difficulty in obtaining continued permission for African tenants to reside on his company's farms in the Pilgrims Rest district. Unless it was possible to continue to obtain such permission, he wrote, 'the effect on the native labour force, both as regards quantity and quality, may be serious and grow progressively worse'. Thus commenced a struggle over the occupation and use of the land which endured for more than two decades, and ended with the final expulsion of the people in 1972. As in so many other land clearances, most people from the farms ultimately found themselves in squalid circumstances, deprived of access to farmland and excluded from the benefits of agricultural progress. As in forced relocation elsewhere in South Africa, legal provisions, courts and the power of the state were all beyond the control of the people affected. But whatever its outcome, the story of the people of these farms is by no means simply one of the 'apartheid state' bulldozing its hapless victims into an inevitable submission. This complex conflict variously pitted the company, the state and the people on the farms against one another, with variations of texture in the actions of various parties and subtle divisions within the state and the company as well as the farm communities.
African Studies Seminar series. Paper presented June 1985
Keywords: Farm tenancy. Social aspects. South Africa. Pilgrim's Rest; Land use. South Africa. Pilgrim's Rest; Eviction. South Africa. Pilgrim's Rest